Use of orange peel (citrus sinensis) in the bioabsorption of potentially toxic metals from water resources through ICP-OES - Lima, Jayra Maria Silva; Souza, Hellen Dianne Pereira de; Cunha, José Renato Matos Sucupira (Ciência e Natura, 2022)
Water is the main resource for the world and humankind subsistence, being also used as a way to conduct nutrients and essential substances to life. The objective of this research was to evaluate the use of orange peel (Citrus sineses) as an adsorbent in water contaminated by heavy metals. To investigate this question, the group used calculations to know the recovery percentage of each analyzed metal, using 0.5g of adsorbent in solutions containing metals (Pb, Fe, Zn, Ni and Mn) with previously known concentrations in mg L-1. The metal analyzes were performed in an inductively coupled plasma atomic emission spectrometer (ICP-OES). The analysis of the response surfaces indicated that the greater mass of adsorbent there was a greater adsorption rate. Based on the obtained responses, 13 mg L-1 of Pb were reduced to 0.44 mg L-1, using 0.5 g of adsorbent, resulting in 96.7% of efficiency for the applied methodology. There was removal of metals in higher concentrations bands and mass, presenting efficiencies from 64.3% to 98.2%. The orange peel was adequate as an adsorbent for the removal of heavy metals from the solution.